Method for preparing high-strength concrete from all-solid waste cementing material
By mixing all solid waste gelling materials with water reducing agent first and gradually mixing them with water, fine aggregate and coarse aggregate to form high-strength concrete, the problem of insufficient compressive strength of existing concrete is solved and significant Increase compressive strength and stable strength growth.
Patent Information
- Application Number
- CN202411553965.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-11
AI Technical Summary
The compressive strength of existing concrete prepared by re-adding steel slag, slag and desulfurized gypsum powder still needs to be improved.
The all-solid waste gelling material and water reducing agent are used to mix evenly first, and then gradually mix evenly with water, fine aggregate and coarse aggregate to form high-strength concrete.
The compressive strength of concrete has been significantly improved, the early strength growth is good, the later strength growth is stable, the 3d compressive strength can increase by more than 30%, and the 7d and 28d compressive strength can reach more than 40%.
Smart Images

Figure BDA0005116175340000071 
Figure BDA0005116175340000091 
Figure BDA0005116175340000092
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid waste treatment, and in particular to a method for preparing high-strength concrete using all-solid waste cementitious materials. Background Art
[0002] During the rapid development of modern industry, a large amount of industrial solid waste has been generated, which not only causes a waste of resources, but also leads to environmental pollution. A large amount of research and application practice of industrial solid waste such as steel slag, slag, fly ash as concrete admixtures have shown that the compounding of multiple admixtures can play a good role in improving the performance of concrete in all aspects. However, the compressive strength of concrete prepared by compounding steel slag, slag and desulfurized gypsum powder still needs to be improved. Summary of the invention
[0003] In view of this, the present invention provides a method for preparing high-strength concrete using all-solid waste cementitious materials. The concrete provided in this application has high compressive strength.
[0004] The present application provides a method for preparing high-strength concrete using all-solid waste cementitious materials, comprising the following steps:
[0005] The all-solid waste cementitious material and the water reducing agent are evenly mixed, then evenly mixed with water, then evenly mixed with fine aggregate, and then evenly mixed with coarse aggregate to obtain concrete.
[0006] In some specific implementations, the all-solid waste gelling material includes:
[0007] 45 wt% to 50 wt% CaO;
[0008] 15 wt% to 20 wt% SiO2;
[0009] 13 wt% to 18 wt% Fe2O3;
[0010] 8wt% to 12wt% Al2O3;
[0011] 3 wt% to 5 wt% MgO;
[0012] 7wt% to 8wt% of others.
[0013] In some specific implementations, the all-solid waste gelling material includes:
[0014] 10wt% to 30wt% of steel slag powder;
[0015] 60 wt% to 80 wt% of slag powder; and
[0016] 10wt% to 15wt% of desulfurized gypsum powder.
[0017] In some specific implementations, the mass ratio of the all-solid waste cementitious material, water, fine aggregate and coarse aggregate is 20-22:5-7:23-25:48-50;
[0018] The amount of the water reducing agent used is 0.3wt% to 0.4wt% of the all-solid waste cementitious material.
[0019] In some specific implementations, the water reducer is selected from polycarboxylate water reducer.
[0020] In some specific implementations, the particle size of the fine aggregate is less than 5 mm.
[0021] In some specific implementations, the particle size of the coarse aggregate is 5 mm to 20 mm.
[0022] In some specific implementations, the fine aggregate and the coarse aggregate are independently selected from at least one of basalt, crushed stone and river sand.
[0023] The present application also provides concrete prepared by the method described in the above technical solution.
[0024] In some specific implementations, the compressive strength of the concrete after curing for 28 days is greater than 70 MPa.
[0025] The method for preparing high-strength concrete with all-solid waste cementitious materials provided in the present application comprises mixing all-solid waste cementitious materials and water reducers evenly, then mixing them evenly with water, then mixing them evenly with fine aggregates, and then mixing them evenly with coarse aggregates to obtain concrete. Compared with mixing all-solid waste cementitious materials, water, water reducers, fine aggregates and coarse aggregates all at once, the present application mixes all-solid waste cementitious materials with water reducers, water, fine aggregates and coarse aggregates in sequence, which can greatly improve the compressive strength of concrete, and the prepared concrete has good early strength growth and stable later strength growth. The experimental results show that the method provided in the present application can improve the compressive strength of concrete prepared with all-solid waste cementitious materials prepared with steel slag powder, slag powder and desulfurized gypsum, and the 3d compressive strength can be increased by more than 30%, the 7d compressive strength and the 28d compressive strength can be increased by more than 40%, and the slump of the obtained concrete is between 195 and 205, the initial setting time is about 60 minutes, and the final setting time is about 420 minutes. Furthermore, by adjusting the formula of steel slag powder, slag powder and desulfurized gypsum, the compressive strength of the prepared concrete can reach more than 35MPa after 3 days of curing, more than 55MPa after 7 days of curing, and more than 70MPa after 28 days of curing. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The diffraction pattern of the gelled material prepared in Example 8;
[0027] Figure 2 The concrete strength test curves prepared in Examples 1 to 8;
[0028] Figure 3 This is the concrete strength test curve prepared in Comparative Examples 1 to 8. DETAILED DESCRIPTION
[0029] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.
[0031] In addition, the terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, "multiple" means two or more, unless otherwise clearly and specifically defined. In addition, the terms "installed", "connected" and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal connection of two components. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0032] The present application provides a method for preparing high-strength concrete using all-solid waste cementitious materials, comprising the following steps:
[0033] The all-solid waste cementitious material and the water reducing agent are evenly mixed, then evenly mixed with water, then evenly mixed with fine aggregate, and then evenly mixed with coarse aggregate to obtain concrete.
[0034] Compared with mixing all solid waste cementitious materials, water, water reducer, fine aggregate and coarse aggregate, the method of first mixing all solid waste cementitious materials and water reducer evenly, then mixing with water, then mixing with fine aggregate, and then mixing with coarse aggregate evenly can greatly improve the compressive strength of concrete, and the prepared concrete has good early strength growth and stable later strength growth. The experimental results show that the method provided by the present application can improve the compressive strength of concrete prepared by all solid waste cementitious materials prepared by steel slag powder, slag powder and desulfurized gypsum, and the 3d compressive strength can be increased by more than 30%, the 7d compressive strength and 28d compressive strength can reach more than 40%, and the slump of the obtained concrete is between 195 and 205, the initial setting time is about 60 minutes, and the final setting time is about 420 minutes. Furthermore, by adjusting the formula of steel slag powder, slag powder and desulfurized gypsum, the compressive strength of the prepared concrete can reach more than 35MPa after 3 days of curing, more than 55MPa after 7 days of curing, and more than 70MPa after 28 days of curing.
[0035] The present application uses all-solid waste cementitious materials, water, water reducing agent, fine aggregate and coarse aggregate as raw materials to prepare concrete, wherein the all-solid waste cementitious materials are materials prepared by mixing solid wastes such as steel slag, slag, fly ash, iron tailings, desulfurized gypsum powder, etc., and have cementitious properties.
[0036] In some specific implementations, in terms of composition, the all-solid waste cementitious material includes:
[0037] 45 wt% to 50 wt% CaO;
[0038] 15 wt% to 20 wt% SiO2;
[0039] 13 wt% to 18 wt% Fe2O3;
[0040] 8wt% to 12wt% Al2O3;
[0041] 3 wt% to 5 wt% MgO;
[0042] 7wt% to 8wt% of others.
[0043] In some specific implementations, other components are related to the raw materials used, and this application has no special restrictions on them. For example, they can be:
[0044] 2 wt% to 3 wt% S;
[0045] 1 wt% to 2 wt% TiO2;
[0046] 1 wt% to 2 wt% of MnO;
[0047] 0.1 wt% to 1 wt% C;
[0048] 0.1 wt% to 1 wt% K2O;
[0049] 0.1wt% to 1wt% P2O5;
[0050] 0.1wt% ~ 1wt% Na2O, etc.
[0051] In some specific implementations, in terms of the preparation of raw materials, the all-solid waste gelling material includes:
[0052] 10wt% to 30wt% of steel slag powder;
[0053] 60 wt% to 80 wt% of slag powder; and
[0054] 10wt% to 15wt% of desulfurized gypsum powder.
[0055] Steel slag is a by-product of the steelmaking process. It is composed of various oxides formed by oxidation of impurities such as silicon, manganese, phosphorus, and sulfur in pig iron during the smelting process, as well as salts generated by the reaction of these oxides with solvents. The present application has no special restrictions on the composition and source of the steel slag. Any steel slag that can be obtained by those skilled in the art can be used. In some specific implementations, the particle size of the steel slag powder is less than 300 mesh. In some specific implementations, the amount of the steel slag powder is 15wt% to 30wt%, preferably 20wt% to 30wt%, and more preferably 25wt% to 30wt%. In some specific implementations, the steel slag has the following composition:
[0056] SiO2: 28wt%~35wt%; CaO: 38wt%~45wt%; MgO: 5wt%~10wt%; Al2O3: 10wt%~15wt%; FeO: 0.5wt %~1wt%; TiO2: 0.5wt%~1wt%; S: 1wt%~1.5wt%; MnO: 0.2wt%~0.5wt%; Alkalinity R: 1.15wt%~1.25wt%.
[0057] Slag is a by-product of the blast furnace ironmaking process. During the ironmaking process, iron oxide is reduced to metallic iron at high temperature, and impurities such as silicon dioxide and aluminum oxide in the iron ore react with lime and the like to form a molten material with silicates and aluminosilicates as the main components. After quenching, it becomes a loose, porous granular material, which is blast furnace slag, referred to as slag. This application does not have any special restrictions on the composition and source of the slag, and any slag that can be obtained by those skilled in the art can be used. In some specific implementations, the particle size of the slag powder is less than 300 mesh. In some specific implementations, the amount of the slag powder is 60wt% to 75wt%, preferably 60wt% to 70wt%, and more preferably 60wt% to 65wt%. In some specific implementations, the slag has the following composition:
[0058] CaO: 40wt%~50wt%; SiO2: 10wt%~15wt%; TFe: 0~16wt%; MgO: 8wt%~13wt%; Al2O3 : 1.5wt%~2.5wt%; P2O5: 1.5wt%~3wt%; MnO: 2.5wt~5wt%; Alkalinity R: 2.8wt%~3.5wt%.
[0059] Desulfurization gypsum (English name desulfurization gypsum) is also called flue gas desulfurization gypsum, sulfur gypsum or FGD gypsum. Its main component is the same as natural gypsum, which is calcium sulfate dihydrate CaSO4·2H2O, and its content is ≥93%. Desulfurization gypsum is a by-product of the FGD process. The FGD process is a technology that uses lime-limestone to recover sulfur dioxide in the flue gas of coal or oil. This technology is to grind lime-limestone into slurry, and pass the flue gas containing SO2 after dust removal through a slurry scrubber to remove SO2. The lime slurry reacts with SO2 to generate calcium sulfate and calcium sulfite, and the calcium sulfite is oxidized to calcium sulfate to obtain industrial by-product gypsum, which is called desulfurization gypsum. This application does not have any special restrictions on the composition and source of the desulfurization gypsum powder, and the desulfurization gypsum powder that can be obtained by those skilled in the art is sufficient. In some specific implementations, the particle size of the desulfurization gypsum powder is less than 300 meshes. In some specific implementations, the desulfurized gypsum has the following composition: CaO: 85wt% to 95wt%, SiO2: 4wt% to 5wt%; MgO: 0.5wt% to 1wt%.
[0060] The present application uses steel slag powder, slag powder and desulfurized gypsum powder as raw materials, and mixes them evenly to prepare the cementitious material. The present application has no special restrictions on the mixing method, and methods such as ball milling well known to those skilled in the art can be used.
[0061] In the present application, the divalent metal oxides and hydroxides in the steel slag cooperate with the desulfurized gypsum to stimulate the slag and the like to form a gelling material with gelling properties, and are used to prepare concrete. Among them, the total content of divalent metal oxides (CaO+MgO+FeO) in the steel slag is relatively high, for example, it can reach 72.3wt%. These metal oxides are not only the material basis for stimulating the slag and steel slag to form CSH gel, but also the material basis for taking away the A12O3 and Fe2O3 in the slag and steel slag with the participation of desulfurized gypsum to form iron-containing calcium sulfonate complex salts. The content of silicon (aluminum) oxygen tetrahedrons with potential hydraulic activity in the slag is relatively high. The CSH gel that contributes the most to the strength of concrete is a chain-structured silicate formed by connecting silicon (aluminum) oxygen tetrahedrons. Moreover, the molar ratio of (SiO2+Al2O3) / (CaO+MgO) in the slag is relatively high, which also has a large contribution to the formation of CSH gel. The experimental results show that the all-solid waste cementitious material prepared when the steel slag powder dosage G is 30%>G≥25%, the slag powder dosage K is 65%>K≥60%, and the desulfurized gypsum powder T is 15%>T≥10% has the best strength after being prepared into concrete.
[0062] The present application uses a water reducer as a raw material, and the water reducer is preferably a polycarboxylate water reducer. Compared with other water reducers, the polycarboxylate water reducer has the characteristics of low dosage and high water reduction rate.
[0063] The present application uses coarse aggregate and fine aggregate as raw materials, wherein the particle size of the coarse aggregate is larger than that of the fine aggregate, for example, the particle size of the fine aggregate is less than 5 mm, and the particle size of the coarse aggregate is 5 mm to 20 mm. The present application has no special restrictions on the materials of the coarse aggregate and the fine aggregate, which are independently selected from basalt, crushed stone, river sand, waste stone, waste sand, etc. Specifically, the coarse aggregate and the fine aggregate described in the present application can be the above materials crushed by a crusher, and the materials with specific particle sizes are selected, and the present application has no special restrictions on this.
[0064] The present application has no special restrictions on the water used, and tap water can be used.
[0065] In some specific implementations, the mass ratio of the all-solid waste cementitious material, water, fine aggregate and coarse aggregate is 20-22:5-7:23-25:48-50, preferably 20.5-21.5:5.5-6.5:48.5-49.5.
[0066] In some specific implementations, the amount of the water reducing agent used is 0.3wt% to 0.4wt% of the all-solid waste cementitious material, preferably 0.4wt%.
[0067] Different from the method of all-feeding and then mixing disclosed in the prior art, the present invention first mixes the solid waste cementitious material and the water reducer evenly, then mixes with water, then mixes with fine aggregate, and then mixes with coarse aggregate, which can be called a three-stage feeding method. The present invention has no special restrictions on the mixing method, and the mixing can be carried out in a mixer.
[0068] The present application firstly mixes the all-solid waste cementitious material and the water reducer evenly and then mixes them evenly with water, and utilizes the synergistic excitation effect of steel slag powder, desulfurized gypsum powder and slag powder to form a large number of needle-rod-shaped complex salt crystals, and also forms a large number of nearly amorphous CSH gels and zeolite-like phases, and tightly wraps the needle-rod-shaped complex salt crystals, thereby greatly improving the stability of the entire system.
[0069] In this application, steel slag powder, desulfurized gypsum powder and slag powder play a synergistic role, generating calcium vanadate (AFt) and hydrated calcium silicate gel (CSH) through the hydration process, which play a hardening and strengthening role. The process is as follows:
[0070]
[0071] The present application mixes all-solid waste cementitious materials and water reducer evenly, then mixes them evenly with water, then mixes them evenly with fine aggregate, and finally mixes them with coarse aggregate, which has a positive promoting effect on the improvement of concrete strength and can greatly improve the compressive strength of concrete.
[0072] The present application also provides a concrete prepared by the method described in the above technical solution. In some specific implementations, the compressive strength of the concrete can reach more than 35MPa after curing for 3 days, more than 55MPa after curing for 7 days, and more than 70MPa after curing for 28 days, which is more than 30% higher than the corresponding compressive strength of the concrete obtained by all mixing; and the slump of the obtained concrete is between 195 and 205, the initial setting time is about 60min, and the final setting time is about 420min.
[0073] The method for preparing high-strength concrete with all-solid waste cementitious materials provided in the present application comprises the following steps: firstly, the all-solid waste cementitious materials and the water reducer are uniformly mixed, then mixed with water, then mixed with fine aggregate, and then mixed with coarse aggregate to obtain concrete. Compared with the method of mixing all-solid waste cementitious materials, water, water reducer, fine aggregate and coarse aggregate, the method of first mixing all-solid waste cementitious materials and the water reducer uniformly, then mixing with water, then mixing with fine aggregate, and then mixing with coarse aggregate in the present application can greatly improve the compressive strength of concrete, and the prepared concrete has better early strength growth and stable later strength growth.
[0074] The method for preparing high-strength concrete using all-solid waste cementitious materials provided in the present application is described in detail below in conjunction with the embodiments.
[0075] In the following embodiments, the slag powder comes from blast furnace slag after blast furnace ironmaking, and its composition is as follows:
[0076] SiO2: 28wt%~35wt%; CaO: 38wt%~45wt%; MgO: 5wt%~10wt%; Al2O3: 10wt%~15wt%; FeO: 0.5wt%~1wt%; TiO2: 0.5wt%~1wt%; S: 1wt%~1.5wt%; MnO: 0.2wt%~0.5wt%; Rare earth R: 1.15wt%~1.25wt%;
[0077] Steel slag powder comes from converter slag, refined slag and other steel slag formed by converter steelmaking, and its composition is as follows:
[0078] CaO: 40wt%~50wt%; SiO2: 10wt%~15wt%; TFe: 0~16wt%; MgO: 8wt%~13wt%; Al2O3 : 1.5wt%~2.5wt%; P2O5: 1.5wt%~3wt%; MnO: 2.5wt~5wt%; Alkalinity R: 2.8wt%~3.5wt%;
[0079] Desulfurized gypsum comes from the by-product of sintering desulfurization in steel plants, and its composition is as follows:
[0080] CaO: 85wt% ~ 95wt%, SiO2: 4wt% ~ 5wt%; MgO: 0.5wt% ~ 1wt%.
[0081] Examples 1 to 8
[0082] The slag powder, steel slag powder and desulfurized gypsum were crushed to 300 meshes, and mixed evenly according to the ratio shown in Table 1 to prepare the all-solid waste cementitious material. The cementitious material prepared in Example 8 was subjected to diffraction analysis, and the results are shown in Figure 1 , Figure 1 The diffraction pattern of the gelled material prepared in Example 8 is Figure 1 It can be seen that the strongest peak intensities of the gelling material are: CaSO4-62, FeO-53, Ca2SiO4-35, CaCO3-29, Fe2O3(CaO)2-25, etc.
[0083] Referring to the C40 grade concrete prepared by cement-based, according to the requirements of the cement-based standard "GB / T50107-2010 Concrete Strength Test and Evaluation Standard", a concrete test block that meets the requirements is prepared, which specifically includes the following steps:
[0084] The all-solid waste cementitious material and the polycarboxylate water-reducing agent accounting for 4‰ of the all-solid waste cementitious material are mixed according to the proportion shown in Table 3, and then water is added to mix evenly, and then river sand (fine aggregate) with a particle size of less than 5mm is added, and then basalt crushed stone (coarse aggregate) with a particle size of 5mm-20mm is added. After mixing evenly, it is poured into a mold with a size of 100mm×100mm×100mm, and then vibrated and formed using a vibrator. The formed test block is placed in a standard curing box with a temperature of about 20°C and a humidity of more than 90%. After curing for 24 hours, the mold is removed, and the test block is demolded and taken out and continued to be placed in the curing box for curing. According to the requirements of "GB / T50081-2002 Standard for Test Methods for Mechanical Properties of Ordinary Concrete", the compressive strength of concrete test blocks with different curing ages (3d, 7d, 28d) is tested using a pressure testing machine. The results are shown in Table 3. Figure 2 Table 3 shows the test results of concrete properties prepared in Examples 1 to 8. Figure 2 This is the concrete strength test curve prepared in Examples 1 to 8.
[0085] The slump, initial setting time and final setting time of the concrete were tested. The results are shown in Table 3. Table 3 shows the test results of the concrete properties prepared in Examples 1 to 8.
[0086] Table 1 Composition of all-solid waste gelling raw materials prepared in Examples 1 to 8
[0087] Components Steel slag powder Slag powder Desulfurized gypsum powder Example 1 15% 82% 3% Example 2 15% 78% 7% Example 3 15% 73% 12% Example 4 15% 70% 15% Example 5 13% 75% 12% Example 6 17% 71% 12% Example 7 21% 67% 12% Example 8 25% 63% 12%
[0088] Table 2 Composition of concrete raw materials prepared in Examples 1 to 8
[0089]
[0090] Table 3 Concrete strength performance results prepared in Examples 1 to 8
[0091]
[0092]
[0093] Comparative Examples 1 to 8
[0094] The difference from Examples 1 to 8 is that the coarse aggregate, fine aggregate, all-solid waste cementitious material, water and water reducing agent are mixed and stirred evenly. Other conditions are the same. The results are shown in Tables 4 and Figure 3 Table 4 shows the concrete strength test results prepared in Comparative Examples 1 to 8. Figure 3 This is the concrete strength test curve prepared in Comparative Examples 1 to 8.
[0095] The slump, initial setting time and final setting time of the concrete were tested. The results are shown in Table 3, which shows the performance test results of the concrete prepared in the examples of the present application.
[0096] Table 4 Concrete strength test results prepared in Comparative Examples 1 to 8
[0097]
[0098] As can be seen from Tables 3 and 4, the method provided in this application can improve the compressive strength of concrete prepared from all-solid waste cementitious materials prepared from steel slag powder, slag powder and desulfurized gypsum, and the 3d compressive strength can be increased by more than 30%, and the 7d compressive strength and 28d compressive strength can reach more than 40%. Furthermore, by adjusting the formula of steel slag powder, slag powder and desulfurized gypsum, the compressive strength of the prepared concrete can reach more than 35MPa after 3 days of curing, more than 55MPa after 7 days of curing, and more than 70MPa after 28 days of curing.
[0099] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing high-strength concrete using all-solid waste cementitious materials, comprising the following steps: The all-solid waste cementitious material and the water reducing agent are evenly mixed, then evenly mixed with water, then evenly mixed with fine aggregate, and then evenly mixed with coarse aggregate to obtain concrete.
2. The method according to claim 1, characterized in that The all-solid waste gelling material comprises: 45 wt% to 50 wt% CaO; 15 wt% to 20 wt% SiO2; 13 wt% to 18 wt% Fe2O3; 8wt% to 12wt% Al2O3; 3 wt% to 5 wt% MgO; 7wt% to 8wt% of others.
3. The method according to claim 2, characterized in that The all-solid waste gelling material comprises: 10wt% to 30wt% of steel slag powder; 60 wt% to 80 wt% of slag powder; and 10wt% to 15wt% of desulfurized gypsum powder.
4. The method according to claim 3, characterized in that The mass ratio of the all-solid waste cementitious material, water, fine aggregate and coarse aggregate is 20-22:5-7:23-25:48-50; The amount of the water reducing agent used is 0.3wt% to 0.4wt% of the all-solid waste cementitious material.
5. The method according to claim 4, characterized in that The water reducer is selected from polycarboxylate water reducer.
6. The method according to claim 4, characterized in that The particle size of the fine aggregate is less than 5 mm.
7. The method according to claim 4, characterized in that The particle size of the coarse aggregate is 5 mm to 20 mm.
8. The method according to claim 6 or 7, characterized in that: The fine aggregate and the coarse aggregate are independently selected from at least one of basalt, crushed stone and river sand.
9. Concrete prepared by the method according to any one of claims 1 to 8.
10. The concrete according to claim 8, characterized in that Its compressive strength after 28 days of curing is greater than 70MPa.
Citation Information
Cited By
Cementing material in-situ reinforcing agent and early-strength all-solid waste cementing material
CN120903865A
All-solid waste gel tough composite material and preparation method thereof
CN121159218A